Keterlibatan Ayah Dalam Proses Konseling Keluarga : Dampak dan Strategi - Sona, Dwi; Wahyu Irawan, Andi; Wahyu Irawan, Wahyu Widyatmoko (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
This research aims to examine the influence of father involvement in the family counseling process, as well as identify effective strategies to increase father participation in therapy sessions. This study used quantitative and qualitative approaches to collect data from families who attended family counseling at three therapy centers in a large city. Quantitative data were obtained through questionnaires assessing the father's level of involvement and perceived therapy outcomes, while in-depth interviews with fathers, mothers, and therapists provided qualitative insight into their experiences and perceptions. The results showed that fathers' active involvement in family counseling was positively related to improving children's emotional health and the quality of family relationships. Factors influencing father participation include work schedule, perception of the value of therapy, and method of counseling approach used. The study also found that strategies such as flexible scheduling, inclusive counseling approaches, and education about the benefits of father involvement can increase their participation.